Wood smoke particles from different combustion phases induce similar pro-inflammatory effects in a co-culture of monocyte and pneumocyte cell lines - Bølling, Anette Kocbach (BioMed Central, 2012)
BACKGROUND: Exposure to particulate matter (PM) has been linked to several adverse cardiopulmonary effects, probably via biological mechanisms involving inflammation. The pro-inflammatory potential of PM depends on the particles’ physical and chemical characteristics, which again depend on the emitting source. Wood combustion is a major source of ambient air pollution in Northern countries during the winter season. The overall aim of this study was therefore to investigate cellular responses to wood smoke particles (WSPs) collected from different phases of the combustion cycle, and from combustion at different temperatures. RESULTS: WSPs from different phases of the combustion cycle induced very similar effects on pro-inflammatory mediator release, cytotoxicity and cell number, whereas WSPs from medium-temperature combustion were more cytotoxic than WSPs from high-temperature incomplete combustion. Furthermore, comparisons of effects induced by native WSPs with the corresponding organic extracts and washed particles revealed that the organic fraction was the most important determinant for the WSP-induced effects. However, the responses induced by the organic fraction could generally not be linked to the content of the measured polycyclic aromatic hydrocarbons (PAHs), suggesting that also other organic compounds were involved. CONCLUSION: The toxicity of WSPs seems to a large extent to be determined by stove type and combustion conditions, rather than the phase of the combustion cycle. Notably, this toxicity seems to strongly depend on the organic fraction, and it is probably associated with organic components other than the commonly measured unsubstituted PAHs.